2011
DOI: 10.2214/ajr.10.6203
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Cranial Sonography: Part 2, Pitfalls and Variants

Abstract: In this part of the article, we will describe pitfalls and variants that may be confused with pathologic abnormalities. Emphasis will be placed on recognizing normal variations and distinguishing them from pathologic abnormalities that may require additional imaging or clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Also, these hyperechoic pseudolesions and halos are less echogenic than the adjacent choroid plexus. 7,32,33 One well documented example is the thalamic pseudolesion, a hyperechoic focus in the thalamus with the appearance of a central thalamic hemorrhage seen when imaging through the posterior fontanel. The hyperechoic focus is no longer seen when imaging through the anterior fontanel.…”
mentioning
confidence: 99%
“…Also, these hyperechoic pseudolesions and halos are less echogenic than the adjacent choroid plexus. 7,32,33 One well documented example is the thalamic pseudolesion, a hyperechoic focus in the thalamus with the appearance of a central thalamic hemorrhage seen when imaging through the posterior fontanel. The hyperechoic focus is no longer seen when imaging through the anterior fontanel.…”
mentioning
confidence: 99%
“…Although reference charts of normal ventricular sizes are available, the morphology of the ventricles may be the best determinant of ventriculomegaly. 40,84 Although beyond the scope of the current review and not specifically discussed, in the detection of IVH, the use of alternate acoustic windows, such as the posterior fontanelle or the mastoid fontanelle, may increase the detection rate, particularly of grade II IVH, which may be present only in the occipital horns. 35,85 Callosal Abnormalities Abnormalities of the corpus callosum have received little attention in relation to NE, or more specifically HII, although regional or global callosal thinning is a well-known late finding in perinatal brain injury.…”
Section: Ventricular Sizementioning
confidence: 99%
“…[32][33][34] In describing lesser-known US findings in NE, either due to HII or other causes, we reinforce the significant role US can play as a first-line imaging tool, which can be indispensable during the evaluation of critically ill neonates or can complement magnetic resonance imaging (MRI) in more stable neonates. [35][36][37][38][39][40][41] This imaging update draws heavily on the experience of Epelman et al, 39 whose 29-month experience with a cohort of patients with NE receiving concurrent US and MRI guides this discussion. The study advocates high-quality, real-time evaluation with linear, high-resolution transducers.…”
Section: Figurementioning
confidence: 99%
“…Mild ventricular asymmetry is considered to be a normal variantwhich has been described in up to 90% of normal newborn infants [1,3,4]. It has been reported that the larger ventricle is more commonly on the left side [5].…”
Section: Normal Ventriclesmentioning
confidence: 99%